2017
DOI: 10.1016/j.eururo.2016.07.033
|View full text |Cite|
|
Sign up to set email alerts
|

Subgroups of Castration-resistant Prostate Cancer Bone Metastases Defined Through an Inverse Relationship Between Androgen Receptor Activity and Immune Response

Abstract: We studied heterogeneities at a molecular level in bone metastasis samples obtained from men with castration-resistant prostate cancer. We found differences of possible importance for therapy selection in individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
111
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(121 citation statements)
references
References 36 publications
9
111
1
Order By: Relevance
“…The patient series has been previously described [10, 11] and clinical characteristics are summarized in Supplementary Table 1. Expression of IGF-1R was assessed by immunohistochemistry in 61 biopsies (patients) of which 42 had been previously profiled by whole-genome expression analysis [11] and data was available for functional enrichment analysis, see below. The study was approved by the local ethical review board of Umeå University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient series has been previously described [10, 11] and clinical characteristics are summarized in Supplementary Table 1. Expression of IGF-1R was assessed by immunohistochemistry in 61 biopsies (patients) of which 42 had been previously profiled by whole-genome expression analysis [11] and data was available for functional enrichment analysis, see below. The study was approved by the local ethical review board of Umeå University.…”
Section: Methodsmentioning
confidence: 99%
“…Multivariate modelling by means of orthogonal projections to latent structures (OPLS) was used to extract systematic variation in whole-genome expression data from human PCa bone metastasis samples previously analysed [11], in relation to corresponding IGF-1R IHC score in each sample. OPLS-DA was performed in SIMCA version 14.0 (MKS Umetrics AB, Umeå, Sweden) on mean centred and unit variance scaled gene expression data and validated by cross-validation.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, even at the metastatic level, androgensand more precisely the androgen receptor (AR)-are well known to stimulate proliferation (Bolla et al 2009;Ylitalo et al 2017). However, androgen deprivation therapy (ADT) does not cure PCa, as the disease eventually evolves to castration-resistant PCa (CRPC).…”
mentioning
confidence: 99%
“…However, androgen deprivation therapy (ADT) does not cure PCa, as the disease eventually evolves to castration-resistant PCa (CRPC). At this stage, several molecular mechanisms have been discovered, most of them leading to AR hyperactivation, including AR genomic amplification and mutation (Montgomery et al 2008;Robinson et al 2015;Watson et al 2015;Schweizer and Yu 2017;Ylitalo et al 2017). Consequently, further knowledge of downstream effectors of the AR is necessary to dissect the molecular mechanisms governing PCa progression and develop novel therapeutic approaches.…”
mentioning
confidence: 99%
“…In general, testosterone is considered as an anti-inflammatory while estrogens are more proinflammatory, but several studies show shared effects on immune cells between hormones (indicated in red). References not cited in text: androgens on T helper cells (Sutherland et al 2005, Hepworth et al 2010, Fijak et al 2011, Andersson et al 2015, Wang et al 2017b) and on DCs (Koh et al 2009, Corrales et al 2012; estrogens on T helper cells (Correale et al 1998, Maret et al 2003, Lélu et al 2011, Morse & McNeel 2012, Chen et al 2015 and on DCs (Zhang et al 2004 linked to patient outcomes (Ylitalo et al 2016, Strömvall et al 2017, emphasizing the importance of understanding this biology. The receptor and non-receptor-mediated effects of steroids on innate immune cells have been widely studied in experimental animal models as well as in clinical studies of many diseases (Trigunaite et al 2015, Roved et al 2017.…”
Section: Sex Steroids and The Immune Tumor Microenvironment Effect Ofmentioning
confidence: 99%